Cornelius E. DuPuy journal and notebooks - DuPuy, Cornelius E., -1822.
Journal and notebook kept by DuPuy as a physician on the USS Franklin (Ship of the line) during a voyage down the east coast of South America, around Cape Horn, and up the west coast to Valparaiso, Chile. Also includes a notebook with entries relating to medicine.
Physician.
Collection material in English.
Keywords: United States. -- Navy -- Foreign service -- South America; Franklin (Ship of the line); Voyages and travels; Valparaíso (Chile) -- Description and travel; South America -- Description and travel; Physicians